Goodwill Hunting The Royal New Zealand Ballet - Robertson, Allen (Dance Books Ltd., Alton,Hampshire (UK), 2004)
The Royal New Zealand Ballet. The greatest risk, Milagros, paid the biggest dividend. PALABRAS CLAVE: Royal New Zealand Ballet, fiftieth birthday, Milagros, Javier de Frutos, frENZy, pop ballet, Christopher Hampson.